Genetic diversity of Cryptosporidium spp. including novel identification of the Cryptosporidium muris and Cryptosporidium tyzzeri in horses in the Czech Republic and Poland - Wagnerová, Pavla; Sak, Bohumil; McEvoy, John; Rost, Michael; Matysiak, Agniezska Perec; Ježková, Jana; Kváč, Martin (Parasitology research, 2015)
Faecal samples were collected from 352 horses on 23 farms operating under six different management systems in the Czech Republic and Poland during 2011 and 2012. Farms were selected without previous knowledge of parasitological status. All faecal samples were screened for Cryptosporidium spp. presence using microscopy, following aniline-carbol-methyl violet staining and PCR analysis of the small-subunit (SSU) rRNA and the 60-kDa glycoprotein (gp60) genes. Cryptosporidium muris-positive samples were additionally genotyped at four minisatellite markers: MS1 (encoding a hypothetical protein), MS2 (encoding a 90-kDa heat shock protein), MS3 (encoding a hypothetical protein) and MS16 (encoding a leucine-rich repeat family protein). Cryptosporidium spp. was detected by PCR in 12/352 (3.4%) samples from 4 out of 13 farms. None of the samples tested by microscopy was positive. There was no relationship between Cryptosporidium prevalence and age, sex, diarrhoea or management system; however, Cryptosporidium was found only on farms where horses were kept on pasture during the day and in a stable overnight. Sequence analyses of SSU and gp60 genes revealed the presence of C. muris RN66 (n = 9), Cryptosporidium parvum IIaA15G2R1 (n = 1), Cryptosporidium tyzzeri IXbA22R9 (n = 1), and Cryptosporidium horse genotype VIaA15G4 (n = 1). The C. muris subtypes were identified as MS1-M1, MS2-M4, novel MS2-M7 and MS16-M1 by multilocus sequence of three minisatellite loci. The MS3 locus was not amplified from any isolate. This is the first report of C. tyzzeri and C. muris subtypes from horses.
Keywords: Feces; Male; genetická variace; Genotype; kryptosporidióza; Poland; Česká republika; Cryptosporidiosis; prevalence; mužské pohlaví; nemoci koní; Czech Republic; Animals; ženské pohlaví; zvířata; Prevalence; průjem; koně; Cryptosporidium; genotyp; Diarrhea; Genetic Variation; Female; Polsko; feces; Horse Diseases; Horses